Getting the HOTS with what's in the box: Developing higher order thinking skills within a technology-rich learning environment - McMahon, Graham (Curtin University, 2007)
Educators are divided with regards to the value of computer technology as a learning tool. Some maintain that computers have had little impact on students’ learning; others suggest that computers have the potential to enhance learning. Within this second group there are those who believe that computers are having a significant impact, while others believe that their potential is yet to be realised. The purpose of this study was to examine the relationship between students working in a technology rich environment and their development of higher order, critical and creative, thinking skills. Staff and students from one school participated in this case study. Data were collected by teachers as part of the normal teaching-learning program, supplemented by classroom observations and teacher interviews. In addition, data pertaining to the technology infrastructure was collated from school databases. The data were used to determine the degree of correlation between factors of the learning environment and the extent to which higher order thinking skills (HOTS) were demonstrated by the students. Collations of the statistically significant, and statistically insignificant, correlations allowed relationships between environmental factors and HOTS to be established.The results indicate that studying within a technology-rich learning environment improves students’ higher order thinking skills, determined by measuring their critical and creative thinking. Factors such as length of time spent in the environment have a positive, non-linear effect on the development of critical thinking skills. These factors have no significant correlation with the development of creative thinking skills. The interaction of students’ computer skills and the classroom environmental factors was shown to be complex. Three-dimensional correlations were performed to derive equations that explain these interactions. Students with better developed computing skills scored higher on critical and creative thinking activities. This was most significant for students with better computer programming skills and the ability to competently manipulate Boolean logic. The most significant factors in developing higher order thinking skills were the students’ levels of computer skills, tempered with their attitudes towards computers and computer classes, and the teacher-student relationships within the technology-rich learning environment. The research suggests that in order to develop students' higher order thinking skills schools should endeavour to integrate technology across all of the learning areas. This will allow students to apply technology to the attainment of higher levels of cognition within specific contexts. This will need to be paralleled by providing students the opportunity to develop appropriate computer skills.